2015
DOI: 10.1007/s13364-015-0252-y
|View full text |Cite
|
Sign up to set email alerts
|

Local vs landscape drivers of primate occupancy in a Brazilian fragmented region

Abstract: Understanding the drivers of species distributions in human-dominated landscapes is crucial for proposing sound conservation strategies. Primates are the most studied terrestrial vertebrate taxa, yet still their response to forest loss and fragmentation widely varies among species.In this paper, we assessed the relative influence of local vs landscape features on occupancy of two primate species -the black-fronted titi monkey and the black-pencilled marmoset, in a Brazilian fragmented region. We created detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 59 publications
0
8
0
1
Order By: Relevance
“…In contrast with the other two species, no significant influence of any predictor was found on patch occupancy by C. penicillata. In patches of native vegetation of the Brazilian Atlantic forest and Cerrado, Sales et al (2016) also observed a high occupancy level for marmosets, which did not exhibit a clear relationship with any predictors at either a local or landscape scale. This might be accounted for by the considerable ecological flexibility of the marmosets of this genus (Abreu, De la Fuente, Schiel, & Souto, 2016;Amora, Mendes, & Ferrari, 2013), which allows them to colonize successfully both open and disturbed forests.…”
Section: Resultsmentioning
confidence: 69%
“…In contrast with the other two species, no significant influence of any predictor was found on patch occupancy by C. penicillata. In patches of native vegetation of the Brazilian Atlantic forest and Cerrado, Sales et al (2016) also observed a high occupancy level for marmosets, which did not exhibit a clear relationship with any predictors at either a local or landscape scale. This might be accounted for by the considerable ecological flexibility of the marmosets of this genus (Abreu, De la Fuente, Schiel, & Souto, 2016;Amora, Mendes, & Ferrari, 2013), which allows them to colonize successfully both open and disturbed forests.…”
Section: Resultsmentioning
confidence: 69%
“…Black‐fronted titi monkey populations have experienced declines over the last decades (more than 20% in the past 24 years, Jerusalinksy et al, 2020), mainly due to the degradation of the Atlantic Forest (Ribeiro et al, 2009). Titi monkeys can live in primary and secondary forests (Trevelin et al, 2007) with high and closed canopy (Sales et al, 2016), which enables them to occur in small forest patches embedded in agricultural landscapes (Ribeiro et al, 2009). The inevitable proximity to humans and domestic animals in these landscapes increases the chances of pathogens transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Quatro espécies com registros para o município de Lavras não foram observadas para o campus da UFLA, Callicebus nigrifrons (Primates, Pitheciidae), Puma concolor (Carnivora, Felidae), Euphractus sexcinctus (Cingulata, Dasypodidae) e Conepatus semistriatus (Carnivora, Mephitidae). Populações da espécie C. nigrifrons estão presentes em remanescentes florestais circundantes ao campus, assim como em grande parte dos remanescentes florestais do município (Sales et al 2016). Desse modo, sua ausência na área de estudo ainda não é compreendida.…”
Section: Discussionunclassified